Act of Jan. 31, 1888, § 2 Wash. Territory Sess. Laws 100, 100-101 (Thomas H. Cavanaugh 1888). - (:unkn) unknown (My University, 1888)
Every person who shall, in a manner likely to cause terror to the people passing, exhibit or flourish, in the streets of an incorporated city or unincorporated town, any dangerous weapon, shall be deemed guilty of a misdemeanor, and, on conviction thereof, shall be punished by a fine in any sum not exceeding twenty-five dollars.
Keywords: GOING ARMED